P227 Patient Satisfaction – New LGBTQ (Lesbian, Gay, Bisexual and Queer) Sexual Health Clinic. (30th June 2016) - Cooney, Grainne; Hamlyn, Eleanor; Wallace, Sabrina; Svensson, Ella; Underwood, Michael; Barber, Tristan
Abstract : Background/introduction: This clinic opened in 2015 offering a weekly specialist sexual health service for our LGBTQ community. Burden of pathology is high, suggesting a potentially more stressful environment for patients. All medical and non-medical staff were trained on LGBTQ sexual health issues and some on Club Drug related issues. Aim: To assess patient satisfaction with the new service, a questionnaire was undertaken seven months after service commencement. Methods: Over a four-week period, questionnaires were handed to patients by reception at booking. Thirty-six questionnaires were returned. Results: Patients rated the service as excellent 81% (26/32) very good 14% (5/32) or good 3% (1/32). All patients who answered said they would attend again 100% (32/32). Most would recommend it to a friend 97% (32/33). Patient staff satisfaction was high, with 96% (29/30) stating they felt listened to. Patients felt treated with respect and dignity always 97% (31/32) or sometimes 3% (1/32). 83% (30/36) of patients attended specifically with LGBTQ concerns, of these 93% (28/30) felt confident in discussing concerns with staff, 7% (2/30) to some extent. 77% (24/31) indicated that drugs or alcohol were related to their visit. Only 21% (5/24) felt they could raise this topic with staff and 79% (19/24) stated they couldn't. Discussion: Staff training on managing vulnerable clients' health needs enables confidant and approachable health care. This provides patients with opportunities to verbalise health anxieties, facilitating opportunistic healthcare interventions. Drug and Alcohol training for all staff will enhance the patient care package.